Lactococcus lactis NCC 2287 Alleviates Food Allergic Manifestations in Sensitized Mice by Reducing IL-13 Expression Specifically in the Ileum. (22nd September 2011) - Zuercher, Adrian W.; Weiss, Marietta; Holvoet, Sébastien; Moser, Mireille; Moussu, Hélène; van Overtvelt, Laurence; Horiot, Stéphane; Moingeon, Philippe; Nutten, Sophie; Prioult, Guénolée; Singh, Anurag; Mercenier, Annick
Abstract : Objective . Utilizing a food allergy murine model, we have investigated the intrinsic antiallergic potential of the Lactococcus lactis NCC 2287 strain. Methods . BALB/c mice were sensitized at weekly intervals with ovalbumin (OVA) plus cholera toxin (CT) by the oral route for 7 weeks. In this model, an oral challenge with a high dose of OVA at the end of the sensitization period leads to clinical symptoms. Lactococcus lactis NCC 2287 was given to mice via the drinking water during sensitization (prevention phase) or after sensitization (management phase). Results . Lactococcus lactis NCC 2287 administration to sensitized mice strikingly reduced allergic manifestations in the management phase upon challenge, when compared to control mice. No preventive effect was observed with the strain. Lactococcus lactis NCC 2287 significantly decreased relative expression levels of the Th-2 cytokine, IL-13, and associated chemokines CCL11 (eotaxin-1) and CCL17 (TARC) in the ileum. No effect was observed in the jejunum. Conclusion/Significance . These results taken together designate Lactococcus lactis NCC 2287 as a candidate probiotic strain appropriate in the management of allergic symptoms.